Key Strategies for Physical Activity Interventions Among Older Women: Process Evaluation of a Clinical Trial. Issue 3 (March 2018) - Lefler, Leanne L.; Jones, Sara; Harris, Breanna
Purpose: To describe strategies salient to physical activity (PA) initiation and maintenance among older women who participated in a clinical trial that tested a PA intervention. Design: A descriptive phenomenological, qualitative design for a process evaluation of a successful clinical trial. Setting: Senior primary care clinics associated with a large medical center in a southern state. Participants: A total of 20 older women at least 60 years without advanced frailty. Method: Purposive sampling using maximum variation technique was used to select participants. A semi-structured interview guide facilitated individual, in-depth interviews lasting 45 to 90 minutes. Narratives were analyzed using content analysis with constant comparison technique to summarize the data. Results: Eight African American and 12 white older women with a mean age of 68 from control and intervention arms participated. Five central themes described salient strategies to promote and maintain PA: sensed benefits, motivation, and self-efficacy were central to success, while a reduction in barriers was essential before maintaining PA. The last theme, a life-changing awareness indicated that PA had become a shared value. An explanatory model describing interrelationships is presented. Conclusions: This study suggests key strategies to include in PA interventions with older women. An unexpected finding was that PA became a shared value, an action promoted by the Culture of Health initiative to improve population health and well-being.